Dendritic Glycopolymer as Drug Delivery System for Proteasome Inhibitor Bortezomib in a Calcium Phosphate Bone Cement: First Steps Toward a Local Therapy of Osteolytic Bone Lesions - Striegler, Christin; Schumacher, Matthias; Effenberg, Christiane; Mueller, Martin; Seckinger, Anja; Schnettler, Reinhard; Voit, Brigitte; Hose, Dirk; Gelinsky, Michael; Appelhans, Dietmar (Macromolecular Bioscience, 2015)
Establishment of drug delivery system (DDS) in bone substitute materials for local treatment of bone defects still requires ambitious solutions for a retarded drug release. We present two novel DDS, a weakly cationic dendritic glycopolymer and a cationic polyelectrolyte complex, composed of dendritic glycopolymer and cellulose sulfate, for the proteasome inhibitor bortezomib. Both DDS are able to induce short-term retarded release of bortezomib from calcium phosphate bone cement in comparison to a burst-release of the drug from bone cement alone. Different release parameters have been evaluated to get a first insight into the release mechanism from bone cements. In addition, biocompatibility of the calcium phosphate cement, modified with the new DDS was investigated using human mesenchymal stromal cells.
CRIS-Team Scopus Importer:2023-03-20
Keywords: calcium phosphate bone cement; dendritic glycopolymer; drug release; polyelectrolyte complex